2021
DOI: 10.3390/molecules26061499
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Drug Discovery Based on Natural Product β-Elemene: Anti-Tumor Mechanisms and Structural Modification

Abstract: Natural products are important sources for drug discovery, especially anti-tumor drugs. β-Elemene, the prominent active ingredient extract from the rhizome of Curcuma wenyujin, is a representative natural product with broad anti-tumor activities. The main molecular mechanism of β-elemene is to inhibit tumor growth and proliferation, induce apoptosis, inhibit tumor cell invasion and metastasis, enhance the sensitivity of chemoradiotherapy, regulate the immune system, and reverse multidrug resistance (MDR). Elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 102 publications
0
36
0
Order By: Relevance
“…β-elemene, an extract of the rhizome of Curcuma longa, has been shown in several studies to have broad antitumor activity. It could inhibit tumor growth and proliferation, induce apoptosis, and modulate immunity [ 30 , 31 , 32 ]. β-elemene also exerts anti-inflammatory effects by inhibiting CCl 4 -induced serum TNF-α and endotoxin in rats, and experimentally demonstrated that β-elemene attenuates liver fibrosis [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…β-elemene, an extract of the rhizome of Curcuma longa, has been shown in several studies to have broad antitumor activity. It could inhibit tumor growth and proliferation, induce apoptosis, and modulate immunity [ 30 , 31 , 32 ]. β-elemene also exerts anti-inflammatory effects by inhibiting CCl 4 -induced serum TNF-α and endotoxin in rats, and experimentally demonstrated that β-elemene attenuates liver fibrosis [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the pharmacological studies of the compound in vitro and even in vivo are not evidence that it can be converted into a drug to play a therapeutic role. Structural modification based on effective natural ingredients is expected to help reduce toxicity and enhance therapeutic activity, such as the β-elemene component in the rhizome of Wenyujin has been approved by the China Food and Drug Administration (CFDA) to treat a variety of cancers ( Bai et al, 2021 ). Therefore, in research on the bioactive components of H. cordata , structural modification may be an aspect that needs to be paid attention to.…”
Section: Discussionmentioning
confidence: 99%
“…It exerts a good anti-tumour effect in the human body through comprehensive mechanisms, including inhibition of tumour cell growth and proliferation, apoptosis, blocking tumour cell invasion and metastasis, and immune system regulation. More importantly, in human clinical trials, β-elemene also enhances the sensitivitsy of chemotherapy or radiotherapy and reverses multidrug resistance (MDR) 7 , 9 , 12–15 . After years of experimentation and efforts, elemene oral emulsion (CFDA number H20010338) and elemene injection (CFDA number H10960114) developed by our research team was approved by the China Food and Drug Administration (CFDA) as broad-spectrum anti-tumour drugs in the 1990s 7 Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, in human clinical trials, β-elemene also enhances the sensitivitsy of chemotherapy or radiotherapy and reverses multidrug resistance (MDR) 7 , 9 , 12–15 . After years of experimentation and efforts, elemene oral emulsion (CFDA number H20010338) and elemene injection (CFDA number H10960114) developed by our research team was approved by the China Food and Drug Administration (CFDA) as broad-spectrum anti-tumour drugs in the 1990s 7 Figure 1 .…”
Section: Introductionmentioning
confidence: 99%